230 Systemic lupus erythematosus and rapidly progressive cardiogenic shock. (April 2019) - Umar, Anam; Chang, Eric; Bilal, Muhammad; Bradley, Cinnamon
Abstract : Background: Symptomatic lupus myocarditis is a rare but life-threatening complication of systemic lupus erythematosus (SLE). Clinical manifestation is variable and includes dyspnea, chest pain, peripheral edema, fever, nausea, vomiting, or palpitations. We describe a case of a young female who developed rapid progressive cardiogenic shock secondary to lupus myocarditis. Methods: Not applicable as it is a clinical vignette. The abstract for clinical vignette is attached as a separate document Results: Not applicable as it is a clinical vignette The abstract for clinical vignette is attached as a separate document Conclusions: The diagnosis of lupus myocarditis is usually achieved clinically and with the use of TTE, cardiac MRI or biopsy. However, none of the current diagnostic modalities have established sensitivity or specificity. Our patient only developed significant TTE findings during the late stage, which led to an unfortunate delay in diagnosis. We suggest that physicians should always have a broad differential diagnosis and high clinical suspicion to avoid late diagnosis and mismanagement of patients, especially when dealing with cardiac manifestations of SLE. Funding Source(s): None